Implementation of The Load Balance Method for Mikrotik so that The Network is Stable - Muhammad Soelaiman Rasyid; Harry Witriyono; Yuza Reswan; Monsya Juansen (Penerbit Jurnal Indonesia, 2023)
A stable and reliable network is essential in today's world of communications. One of the challenges in managing a network is ensuring balanced resource use so that no one device is overburdened. The load balance method has proven effective in solving this problem, and in this research, we focus on implementing the load balance method on MikroTik devices to improve network stability.